Integrated Accounting System Performance under Electronic Payment Operations in Public Universities - Ammar Ghazi Ibrahim Al-Ezzi; Ali AbdulQader Majeed Al –Obaida; Qusay Burhan Dawood; Marwa Ibrahim Fadhel (Indonesian Journal of Law and Economics Review, 2026)
General Background: Digital transformation has intensified the use of electronic payment operations within public sector accounting systems. Specific Background: Iraqi public universities, including the University of Diyala, are required to apply electronic payment platforms under an integrated accounting system. Knowledge Gap: Empirical evidence on accounting treatments and practical challenges arising from this adoption remains limited. Aims: This study examines accounting treatments and identifies challenges associated with electronic payment operations in Iraqi universities. Results: The findings show that electronic payments significantly affect the integrated accounting system, with limited impact on bank reconciliation and revenue accuracy, alongside weaknesses in electronic literacy. Novelty: The study offers empirical evidence from an Iraqi university context. Implications: Integrated legal, technical, and capacity-building strategies are essential to strengthen accounting reliability and digital financial transformation.Keywords : Electronic Payment Systems, Accounting Treatments, Integrated Accounting System, Iraqi Public Universities, Digital Financial TransformationHighlight : Electronic payment positively impacts unified accounting systems with 56% correlation strength. Accountants face settlement reconciliation problems due to bank statement timing delays. Electronic literacy deficiency among Iraqi citizens significantly hinders payment system adoption.